41. EVALUATION OF RESULTS OF SURGICAL TREATMENT OF TIBIA PLATEAU USING MINIMALLY INVASIVE SURGERY WITH THE SUPPORT OF 3D PRINTING MODELS PRIOR TO SURGERY AT THONG NHAT HOSPITAL HO CHI MINH CITY (Vietnam Journal of Community Medicine, 2024)
Subject and methods: 61 patients over 18 years old with tibial plateau fractures were treated fixation with plate and screws and minimally invasive surgery at Thong Nhat Hospital – Ho Chi Minh city from January 2019 to January 2023, were divided into 2 groups, in which group 1: 30 patients without 3D printing models and group 2: 31 patients with the support of 3D printing models.Results: A mean follow-up time of 13 ± 3.65 months (group 2) and 12.67 ± 3.3 months (group 1), a mean surgical time of group 2 (126.39 ± 40.51minutes) was shorter than group 1 (146.93 ± 38.87 minutes)(P=0.048), mean blood loss of group 2 (341 ± 115.11 ml) was less than group 1 (409.73 ± 114.87 ml)(P=0.044). The results were good to excellent in 100% with a mean Rasmussen score of group 2: 28.35 ± 3.58, there was no difference in age, hospital stay or treatment outcomes between 2 groups, the near complications were superficial wound infection in 3.22% (group 2) and 6.7% (group 1)(P=0.612) of patients, with no deep venous thrombosis or compartment syndrome observed. Long-term complications included mild pain with weather changes and feeling of an implant under the skin in 7/31 (group 2) and 8/30 (group 1) patients.
Keywords: MIPO; tibial plateau fracture; 3D printing